ANALYSIS OF DIGITAL GOVERNANCE IMPLEMENTATION IN MODERN ORGANISATIONS: CHALLENGES AND SOLUTIONS - Zahara Tussoleha Rony; Franciskus Antonius Alijoyo; Fety Surfaifel (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyse the implementation of digital governance in modern organisations, focusing on identifying the challenges faced and the strategic solutions that can be applied. Digital governance is an important aspect in supporting organisational transformation towards efficiency, transparency, and accountability based on information technology. However, its implementation is not without various obstacles, such as infrastructure constraints, human resource readiness, cyber security, and suboptimal regulations. Through literature review and comprehensive analysis, this study outlines these challenges and formulates strengthening strategies that include technology investment, human resource capacity building, security policies, regulatory collaboration, and technological innovations such as artificial intelligence and big data. The results of this study are expected to provide theoretical contributions as well as practical recommendations for organisations seeking to implement effective and sustainable digital governance.